Revisiting the transits of CoRoT-7b at a lower activity level - Barros, S; Almenara, J; Deleuil, M; Diaz, R; Csizmadia, S; Cabrera, J; Chaintreuil, S; Cameron, A; Hatzes, A; Haywood, R; Lanza, A; Aigrain, S; et al. (EDP Sciences, 2014)
CoRoT-7b, the first super-Earth with measured radius discovered, has opened the new field of rocky exoplanets characterisation. To better understand this interesting system, new observations were taken with the CoRoT satellite. During this run 90 new transits were obtained in the imagette mode. These were analysed together with the previous 151 transits obtained in the discovery run and HARPS radial velocity observations to derive accurate system parameters. A difference is found in the posterior probability distribution of the transit parameters between the previous CoRoT run (LRa01) and the new run (LRa06). We propose this is due to an extra noise component in the previous CoRoT run suspected to be transit spot occultation events. These lead to the mean transit shape becoming V-shaped. We show that the extra noise component is dominant at low stellar flux levels and reject these transits in the final analysis. We obtained a planetary radius, $R_p= 1.585±0.064\,R_{\oplus}$, in agreement with previous estimates. Combining the planetary radius with the new mass estimates results in a planetary density of $ 1.19 ± 0.27\, ρ_{\oplus}$ which is consistent with a rocky composition. The CoRoT-7 system remains an excellent test bed for the effects of activity in the derivation of planetary parameters in the shallow transit regime.